Kebaya Encim Betawi: Ikon Busana Perempuan Betawi - Wirawan, Chintya Hanindhitakirana (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
This study was conducted using a semiotic approach to the Betawi women's kebaya encim. The purpose of this article is to examine the Kebaya Encim Betawi which is the kebaya icon of DKI Jakarta province. What is studied is its uniqueness in the form of models, colors, accessories, and the meanings contained behind each component of this Betawi encim kebaya. This study uses a semiotic approach from Charles S. Peirce which was later developed by Ogden & Richards (1923). This study uses qualitative data obtained through library sources in the form of books, research that has been done by other researchers, research journals, articles, and websites. This article reveals that the model, color, and accessories of the kebaya encim have an important and distinctive meaning, which makes it a symbol or icon that shows the elegance and honor of Betawi women.